1963
DOI: 10.1161/01.cir.28.4.560
|View full text |Cite
|
Sign up to set email alerts
|

Further Observations on the Natural History of Isolated Ventricular Septal Defects in Infancy and Childhood

Abstract: IN THE past few years several reports on the physiologic changes in ventricular septal defect with increasing age, based on serial cardiac catheterization studies, have appeared in the literature.'-'0 The results of these investigations have not been uniform, and variable conclusions have consequently evolved. A number of workers' 4-6 suggested that progressive pulmonary hypertension and rapidly increasing pulmonary vascular obstruction hardly occur in childhood, whereas others7-9 indicated that these changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
1

Year Published

1964
1964
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 21 publications
2
15
0
1
Order By: Relevance
“…This incidence is in accord with earlier reports in the literature [2,17,18,28,35]. These patients were all initially found to have elevated pulmonary arterial pressure and were classified in group 2 and 3.…”
Section: Discussionsupporting
confidence: 91%
“…This incidence is in accord with earlier reports in the literature [2,17,18,28,35]. These patients were all initially found to have elevated pulmonary arterial pressure and were classified in group 2 and 3.…”
Section: Discussionsupporting
confidence: 91%
“…In our other long-term follow-up study, which includes adolescents [28], this was observed in only two patients (1.9%) and PAP had normalized between ages 4 and 6 years in most [30]. Consistent with the duration of the series presented here, the incidence of Eisenmenger syndrome was found to be rare in the first 4 years of life [3,4,6,7,18,40,46,47].…”
Section: Discussionsupporting
confidence: 83%
“…Our results in relation to RVP can therefore not be compared with them. Some, with age and severity grade representing fairly the "natural" distribution of VSD with satisfactory long-term follow-up results, found that the incidence of PH fell significantly and the ratio of Eisenmenger was between 1% and 2% [3,4,48]. Serial hemodynamic studies, however, were selectively done in patients with only moderate or large defects.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Since that time, several groups of workers have further confirmed the phenomenon of spontaneous closure of isolated VSDs both clinically and by angiography. [5][6][7][8][9] This phenomenon is not confined to infants but also occurs in older children and adults. 3,7,10,11 Spontaneous closure has been reported in small and large defects.…”
Section: Introductionmentioning
confidence: 99%